The Effect of Vaccine Literacy on Parental Trust and Intention to Vaccinate after a Major Vaccine Scandal. Issue 5 (4th May 2018) - Wang, Xiaomin; Zhou, Xudong; Leesa, Lin; Mantwill, Sarah
Abstract : Health literacy, and more specifically vaccine literacy, might be an important factor in reducing the negative effects of exposure to misleading reports on vaccination. This study explores the association between vaccine literacy and vaccination-related outcomes after misleading reports on a scandal concerning locally produced childhood vaccines had emerged in 2016 in China. Data for this study came from a cross-sectional survey, which was conducted in April 2016 in Hangzhou, China. Data were collected in kindergartens and community health centers among parents of children up to 6 years of age. Data were analyzed for 1864 participants. Binary logistic regression models showed that, after controlling for socio-demographics and children's age, parents who had better vaccine literacy (<0.05) were more likely to trust and choose domestically produced vaccines, which account for about 95% of the total vaccinations in China. This study provides evidence on a still largely understudied relationship between vaccine literacy and vaccination-related outcomes. Findings might suggest that higher literacy levels could reduce some of the negative effects of being exposed to misleading information on vaccination, eventually leading to less vaccination hesitancy.